2006
DOI: 10.1128/jvi.00553-06
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Organization and Hypoxic Activation of the Kaposi's Sarcoma-Associated Herpesvirus ORF34-37 Gene Cluster

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the etiologic agent for Kaposi's sarcoma (KS) and primary effusion lymphoma (PEL). We previously reported that hypoxia activates KSHV lytic replication and that the promoter for open reading frame 34 (ORF34) contains a functional hypoxia-responsive element (HRE). ORF34 is part of a cluster of lytic genes (ORF34-37) that includes ORF36, a phosphotransferase, and ORF37, a shutoff exonuclease. Rapid amplification of cDNA ends analysis revealed that they share a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
68
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 74 publications
(109 reference statements)
3
68
2
Order By: Relevance
“…In K-Rta-inducible BCBL-1 cells, the 4.2-kb transcript, encoding ORF34 to ORF38, was sensitive to PAA; this finding differs from an earlier report (18). We also detected two additional transcripts (2.0 kb and 0.6 kb) that had not previously been reported (18). These differences in transcription patterns might be caused by the different method for reactivation, i.e., overexpression of the transactivator, K-Rta.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In K-Rta-inducible BCBL-1 cells, the 4.2-kb transcript, encoding ORF34 to ORF38, was sensitive to PAA; this finding differs from an earlier report (18). We also detected two additional transcripts (2.0 kb and 0.6 kb) that had not previously been reported (18). These differences in transcription patterns might be caused by the different method for reactivation, i.e., overexpression of the transactivator, K-Rta.…”
Section: Discussioncontrasting
confidence: 99%
“…Other investigators using microarray analysis, coupled with the use of an inhibitor of viral DNA synthesis, also showed that the vPK gene was expressed early in the viral lytic cycle (31). In K-Rta-inducible BCBL-1 cells, the 4.2-kb transcript, encoding ORF34 to ORF38, was sensitive to PAA; this finding differs from an earlier report (18). We also detected two additional transcripts (2.0 kb and 0.6 kb) that had not previously been reported (18).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This wide repertoire of targets results from vPK localizing within both the cytoplasmic and nuclear compartments (12). Within the KSHV genome, vPK is located within the ORF 34-37 cluster, which contains a hypoxia-inducible factor (HIF) response element within the promoter region (13,14). Thus, vPK expression may be induced in hypoxic environments, independent of lytic replication.…”
mentioning
confidence: 99%